The first dog-origin porcine circovirus type 4 complete genomic sequence have high homology with that of pig-derived strains - Xu, Tong; Chen, Lan; Huang, Bing-Zhou; Zhu, Ling; Sun, Xian-Gang; Lai, Si-Yuan; Ai, Yan-Ru; Zhou, Yuan-Cheng; Xu, Zhi-Wen (Frontiers in Microbiology, 2023)
Porcine circovirus 4 (PCV4) was discovered in 2019 and then proved to be pathogenic to piglets. Nevertheless, few studies were currently available about PCV4 infection in species other than pigs and there is no information about the prevalence of PCV4 in dogs. To fill this gap, 264 dog samples were collected from animal hospitals in the Southwest of China from 2021 to 2022 and screened for PCV4. The detected results showed a low percentage of PCV-4 DNA (1.14%, 3/264), indicating that PCV4 could be identified in dogs in southwest China. Moreover, the complete genome of one PCV4 strain (SCABTC-Dog2022) were obtained successfully and shared a high identity (97.9-99.0%) with other PCV4 strains derived from pigs, dairy cows, raccoon dogs and foxes. The SCABTC-Dog2022 were analyzed together with 51 reference sequences. Phylogenetic tree showed that SCABTC-Dog2022 strain derived from dog were clustered in a closed relative and geographically coherent branch with other PCV4 strains collected from four provinces (Sichuan, Fujian, Hunan and Inner Mongolia) of China. To our knowledge, it is the first detection of PCV4 in dogs globally. The association between PCV4 status and clinical syndromes in dogs deserves additional investigations.